PERAN MEDIA MASSA CETAK TERHADAP PARTISIPASI POLITIK MASYARAKAT DALAM PEMILU KEPALA DAERAH KALIMANTAN TENGAH - Noprianto Dundum (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2018)
The role of mass media print in an effort to increase public participation is expected because the media is able to influence the community in the election of regional heads. Based on this, researchers are motivated to prove that print media has an important role in increasing public participation in 2016 regional elections in Central Kalimantan Province. The objective of the research is the role of printed mass media in influencing political participation in the Central Kalimantan regional elections in 2016-2021 period, the participation of the people in the elections of the regional head of Central Kalimantan in the period 2016-2021. This research was conducted in print media of Central Kalimantan Post in Palangka Raya Central Kalimantan Province, andthere is accessibility in collecting data in public subscribed newspaper Kalteng Pos in Palangka Raya City. The type of research used is descriptive by using qualitative data as the main material of study. The data obtained from the field and from the informants, and a basic description so that it can be found the theme and the results of research indicate the influence of mass media to increase public participation in 2016 regional elections in Central Kalimantan Province, the increase is greatly influenced by factors; information.